Regulation of podJ Expression during the Caulobacter crescentus Cell Cycle - Crymes, William B. (American Society for Microbiology, 1999)
The polar organelle development gene, podJ, is expressed during the swarmer-to-stalked cell transition of the Caulobacter crescentus cell cycle. Mutants with insertions that inactivate the podJ gene are nonchemotactic, deficient in rosette formation, and resistant to polar bacteriophage, but they divide normally. In contrast, hyperexpression of podJ results in a lethal cell division defect. Nucleotide sequence analysis of the podJ promoter region revealed a binding site for the global response regulator, CtrA. Deletion of this site results in increased overall promoter activity, suggesting that CtrA is a negative regulator of the podJ promoter. Furthermore, synchronization studies have indicated that temporal regulation is not dependent on the presence of the CtrA binding site. Thus, although the level of podJ promoter activity is dependent on the CtrA binding site, the temporal control of podJ promoter expression is dependent on other factors.